Modelling of lightweight sandwich structures based on corrugated-cores - Rahman, M. M.; Kadirgama, Kumaran; Bachtiar, Dandi; Siregar, J. P.; Sulaiman, A. S. (2014)
Trapezoidal corrugated-core was fabricated using a 45o profiled mould, and used to form a range of lightweight sandwich structures. The 45o corrugation angle was chosen since it represents an optimal configuration for all combinations of bending and shearing stiffness. The compressive behaviour and failure mechanism in the structures based on two different materials have been investigated experimentally. This research work aims to study the behaviour of trapezoidal corrugated-core subjected to tension and compression stresses, the effect of varying the geometrical parameters on the corrugated-core behaviour and to model the mechanical response of trapezoidal corrugated-core with sandwich structures. Trapezoidal corrugated-cores were made of carbon fibre reinforced plastic (CFRP) and glass fibre reinforced plastic (GFRP). Corrugated composites were designed using conventional manufacturing technique and then bonded to skins using adhesive based on the same material, to produce a range of lightweight sandwich structures. The thickness of the cell walls, number of unit and width cell were used in determining the behaviour of the mechanical structures. The initial failure modes in this corrugated structure are struts buckling, fibre cracking, and delamination in the composite structure. Compression loading was subsequently performed on the trapezoidal corrugated structure, where the compression strength shows increasing for all the corrugation structure. To simulate the mechanical response of the corrugation structure, Finite Element (FE) models were developed using ABAQUS/CAE. The results were compared to measure the experimental outcome. From the finding, the effects of varying the number of unit cell dominate by CFRP are higher than GFRP that 2.08 MPa at three unit cell. It shows that the higher number of unit cells it affects the composite strength. For the effect of cell wall thickness, the results show that the higher the wall thickness, the higher the compression strength. The structures show excellent repeatability in terms of their mechanical response. The mechanical response in compression increases with specimen thickness. For validation between FE result and experimental data, a very good agreement is found between experimental and finite element values. This observation is validated by computing the percentage error between the finite element and the experimental results with average difference around 4.97% in maximum load.